2016
DOI: 10.1128/cvi.00023-16
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Activation by Generalized Modules for Membrane Antigens from Lipid A Mutants of Salmonella enterica Serovars Typhimurium and Enteritidis

Abstract: Invasive nontyphoidal Salmonella (iNTS) disease is a neglected disease with high mortality in children and HIV-positive individuals in sub-Saharan Africa, caused primarily by Africa-specific strains of Salmonella enterica serovars Typhimurium and Enteritidis. A vaccine using GMMA (generalized modules for membrane antigens) from S. Typhimurium and S. Enteritidis containing lipid A modifications to reduce potential in vivo reactogenicity is under development. GMMA with penta-acylated lipid A showed the greatest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 44 publications
4
97
0
Order By: Relevance
“…GMMA were produced from Δ tolR mutants of the same strains used as the source of OAg for the glycoconjugate vaccine ( 26 ). S. Typhimurium and S. Enteritidis GMMA had similar size and OAg-to-protein weight ratio (0.72 and 0.61, respectively) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GMMA were produced from Δ tolR mutants of the same strains used as the source of OAg for the glycoconjugate vaccine ( 26 ). S. Typhimurium and S. Enteritidis GMMA had similar size and OAg-to-protein weight ratio (0.72 and 0.61, respectively) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The integrity and attachment of the inner and outer bacterial cell wall membranes of Salmonella can be altered by disruption of the Tol-Pal system, through deletion of the tolR gene ( 26 , 27 ), resulting in the release of large quantities of GMMA. GMMA are outer membrane vesicles of homogeneous size, typically in the range 40–250 nm, released from the surface of genetically mutated Gram-negative bacteria ( 24 ).…”
mentioning
confidence: 99%
“…enteritidis (Simon et al, 2011) and S. typhimurium (Simon et al, 2013) as part of efforts to combat iNTS (Strugnell et al, 2014). Most importantly, a vaccine using GMMA (generalized modules for membrane antigens) from msbB and pagP (encoding lipid A palmitoyltransferase) deletion mutants of S. typhimurium and S. enteritidis with reduced potential for in vivo reactogenicity showed a slightly higher stimulatory potential than WT S. typhimurium harboring WT lipid A (Rossi et al, 2016). Therefore, in this regard, the Δ lppAB Δ msbB mutant with modified LPS may have some advantages over the Δ lppAB mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Flagellin, a TLR-5 agonist, has been recognized and used as an adjuvant for many vaccines (Hayashi et al, 2001; Yin et al, 2013; Gupta et al, 2014). However, a recent study showed that flagellin was not a major factor for GMMA-mediated immune stimulation against salmonellosis (Rossi et al, 2016). Therefore, the immunogenicity of our mutants either should not be significantly influenced by the decreased flagellar-associated proteins or can be further enhanced in conjunction with the flagellin based adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches are currently in development to deliver the O-antigen to the immune system, including whole cell attenuated bacteria (6), vaccines in which the O-antigen are chemically-(7) or bio-conjugated to carrier proteins (8), synthetic vaccine conjugates (9), and GMMA based vaccines (10). GMMA are outer membrane exosomes from Gram-negative bacteria, genetically modified to induce hyperblebbing and to reduce the reactogenic potential of lipid A (11, 12). GMMA are easy and inexpensive to produce, and highly immunogenic (10, 1316).…”
Section: Introductionmentioning
confidence: 99%